1998
DOI: 10.1097/00006534-199812000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A Method that Preserves Circulation during Preparation of the Pectoralis Major Myocutaneous Flap in Head and Neck Reconstruction

Abstract: The present article describes a method that preserves circulation during the preparation of the pectoralis major myocutaneous flap used in head and neck reconstruction. The major disadvantage of this flap is its poor circulation and consequent partial necrosis. To solve this problem, we analyzed the circulation and hemodynamics of the pectoralis major myocutaneous flap (the perforator of the anterior intercostal branch located about 1 to 2 cm medial to the areola in the fourth intercostal space is important), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 13 publications
0
52
0
1
Order By: Relevance
“…7,12,15,18 This may be due to further devascularization of already ischemic tissues that must then rely solely on the lateral thoracic or anterior intercostal perforators for collateral circulation. 19,20 Other adjunctive techniques for sternal wound closure that do not violate the chest wall or increase the risk of breast ischemia include the use of the rectus abdominis muscle alone 14,16 or omentum. 2,9,10 Both these flaps have known inherent risks even for those with an average body habitus, 2,9,12 and their harvest often is a formidable feat in this extremely obese subset of patients.…”
Section: Resultsmentioning
confidence: 99%
“…7,12,15,18 This may be due to further devascularization of already ischemic tissues that must then rely solely on the lateral thoracic or anterior intercostal perforators for collateral circulation. 19,20 Other adjunctive techniques for sternal wound closure that do not violate the chest wall or increase the risk of breast ischemia include the use of the rectus abdominis muscle alone 14,16 or omentum. 2,9,10 Both these flaps have known inherent risks even for those with an average body habitus, 2,9,12 and their harvest often is a formidable feat in this extremely obese subset of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical techniques for pectus excavatum are largely classified into sternum turnover 5 or sternum elevation. 3,6,7 With regard to turnover techniques, Scheer 8 used the rectus abdominis muscle as the pedicle, and Hirayama et al 9 performed vascular anastomosis of the right and left internal thoracic artery and vein. With regard to elevation techniques, Hoshi et al 5 modified Ravitch's technique and elevated the sternum together with the left internal thoracic artery and vein.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] Kiyokawa et al 12 reported 10% partial or marginal necrosis of the cutaneous paddle and total PMMF necrosis in 1% of 151 patients. Castelli et al 13 have reported that the most frequently encountered complication of PMMF is skin island necrosis (5 partial and 1 total) on 84 consecutive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Skin island necrosis was reported to occur in between 7% and 27% of the flaps. [3][4][5][6][7][8][9][10][11][12][13] Rich blood supply of the nipple-areola complex led us place this unit on the skin island to capture the maximum amount of blood to perfuse the skin paddle. A recent anatomic study by Rikimaru et al 14 on fresh cadavers has suggested that the skin island might include the areola and nipple complex for stabilizing the blood circulation of the skin paddle of the PMMF, which may be grafted back to the original position as a composite graft to achieve better functional and/or esthetic results.…”
mentioning
confidence: 99%